PENGARUH AUDIT INTERNAL, PENGENDALIAN INTERNAL, DAN GOOD GOVERNMENT GOVERNANCE TERHADAP PENCEGAHAN FRAUD DAN IMPLIKASINYA TERHADAP KINERJA PEMERINTAH DAERAH - Ony Widilestariningtyas (Indonesian Journal of Economics and Business, 2012)
Local governments carry out internal audits to provide control over the activities of internal control in the implementation of governance is good, so that fraud can be prevented so that the performance of local government can be carried out adequately.This study aims to determine 1) the relationship between internal audit, internal control and fraud prevention, 2) the influence of internal audit, internal control and good government good governance on the prevention of fraud both simultaneously and parsial, 3) the influence of internal audit, internal control, good government governance, the prevention of fraud on the government's performance both simultaneously and parsial.Unit this study is all the provincial, regency / city in West Java and Banten with respondents Inspectorate West Java and Banten government and the State Audit Representation of West Java and Banten. Method of analysis using Path Analysis.These results indicate that 1) there is a positive relationship between internal audit, internal control and fraud prevention, 2) internal audit, internal control and good government governance affects both fraud prevention and partially simultaneously, 3) internal audit, internal control, good government governance, fraud prevention affects the performance of both local government and partially simultaneously. The contribution of this study describes the effect that the internal audit in the implementation of a consistent internal control for the government to realize good governance and prevent fraud, to improve local government performance on an ongoing basis. The implications of this study showed improved performance of local government for development in the areas of research interest in creating clean government.